A New Paradigm of the Miracles of the Quran: Scientific Interpretation as a Method of Relevance of Revelation to the Challenges of Global Civilization - Nurhuda, Abid; Nawawi, Abd. Muid (Advances in Humanities and Contemporary Studies, 2026)
This study offers a new framework for understanding the miracles of the Quran through the perspective of scientific interpretation, positioning it as a method of relevance of revelation in facing the challenges of global civilization. Until now, the interpretation of Quranic miracles has tended to be divided into two: limited to linguistic beauty or forced to align with tentative scientific theory. The proposed new paradigm shifts this approach toward a dialogical model that integrates revelation with science without being trapped in reductionism. The Quran is read not only as a normative text but as an epistemological horizon and ethical inspiration that guides the direction of development of science, technology, and social policy. This study emphasizes that scientific interpretation must be seen as a transformative medium, not merely an apologetic tool. Kauniyah's verses are understood not only as signs of God's greatness but also as a basis for critical reflection on global issues, such as the ecological crisis, bioethics, and digital disruption. Using a qualitative approach based on literature studies and interdisciplinary analysis, this study highlights the potential of scientific interpretation as a pillar of a new knowledge paradigm that integrates spirituality, rationality, and ethics. The results demonstrate that a new paradigm of Quranic miracles transcends the historical limitations of interpreting miracles, making a tangible contribution to contemporary civilization. Within this framework, Qur'anic miracles are understood as dynamic energies that guide science and technology to remain aligned with humanity and global sustainability. This research recommends developing scientific interpretations within an interdisciplinary praxis, so that the relevance of revelation can stay alive in the face of the complexities of the times.